Vernetzt Zur Entstehung der Netzwerkgesellschaft - Apprich, Clemens (transcript-Verlag, 2016)
Many technologies and practices that have shaped Web 2.0 today date back to the 1990s - and so do the ideas of social media, user-generated content and participatory platforms. Thus, from a media-historical perspective, a lot of the ideas from that period about the future of the Internet have been implemented, albeit without fulfilling the envisioned socio-political utopias. By exploring the history of an alternative web discourse, Clemens Apprich develops a media genealogical understanding which is necessary to think beyond today's pre-dominant concept of socio-technical networks and to intervene in current debates about the Internet
Description based on online resource; title from PDF title page (publisher’s Web site, viewed Jan. 06, 2016)
Keywords: Communication Science, other; Communications; Digitale Medien; Internet; Linguistics, Communication Studies; Medien; Mediengeschichte; Medienökologie; Mediensoziologie; Medienwissenschaft; Netzkritik; Netzkulturen; Netzwerktheorie; Postmoderne; Web 2.0; Kritik; Neue Medien; Medientheorie; World Wide Web 2.0; Online-Community; Hochschulschrift